Cultural Diplomacy as Soft Power in Advancing National Development: A Comparative Study of Nigeria and the United States of America - Tenkorang, N.A. (University of Ghana, 2019)
Culture has been harnessed by states as a diplomatic tool for eons. Its role in fostering cross-cultural and international cooperation is highly noticeable. Intercultural exchanges, especially those initiated by the state or even the private sector, is known to create an atmosphere of friendship and trust, as well as eliminate negative notions held of other cultures. Cultural Diplomacy, as one of the major soft power currencies of states, is used by Nigeria and the U.S., perhaps for a myriad of reasons, however, this study emphasized its role in the social, economic and reputational development of these two countries. This study sought to fill a literary gap which existed on comparative cultural diplomacy and national development. Thus by use of both primary and secondary data, it determined through its two case studies that cultural diplomacy definitely advances national development (although the level of impact differs greatly between the two countries in question) In conclusion of the study. Recommendations such as prioritising cultural diplomacy through funding were made
MA. International Affairs
Keywords: Cultural Diplomacy; World War II; Cold War; Public Diplomacy